Studies Of Antifouling Properties On Ultrafiltration Membrane For Oily Wastewater - Chong, Mei Yan (Universiti Sains Malaysia, 2017)
Organic-inorganic composite membranes were synthesized through phase inversion technique with nano-sized particles such as zinc oxide (ZnO), calcium carbonate (CaCO3) or titanium oxide (TiO2) uniformly dispersed in the polyacrylonitrile (PAN) solution. The effect of nanoparticles and type of nanoparticles were investigated through ultrafiltration process for duration of 360 minutes: 30 minutes of compression, first 100 minutes for pure water flux, second 100 minutes for oily wastewater flux, 30 minutes of membrane cleaning and last 100 minutes for pure water flux. Flux data was recorded and analyzed in terms of flux recovery ratio (FRR), oil rejection rate and fouling resistance evaluation. Characterization of membranes such as contact angle, SEM, FTIR and Porolux were carried out to examine hydrophilicity, surface morphology, surface chemistry and pore size distribution of membranes respectively. Compared with pure PAN membrane, modified membrane showed higher water permeation and better antifouling properties. Besides, titanium oxide (TiO2) was selected as best additive with the highest pure water flux of 225.51 L/m2.h, a maximum FRR of 78.22% and oil rejection rate of 98.96%. It was found that increasing hydrophilicity and reduction in mean pore size resulted in significant increment of pure water flux and nearly perfect oil rejection rate.